Dietary supplementation of ginger (Zingiber officinale) essential oil exhibits positive immunomodulatory effects on the neotropical catfish pseudoplatystoma reticulatum without negative effects on fish liver histomorphometry - Almeida, Rômullo Guilherme Dos Santos; Martins, Mateus Aranha; Oliveira, Fulvia Cristina; Santo, Fayane Espirito; Calves, Gleice Souza; Pilarski, Fabiana [UNESP]; Chagas, Edsandra Campos; Fernandes, Carlos Eurico; Martins, Maurício Laterça; de Campos, Cristiane Meldau (Pontificia Universidad Catolica de Valparaiso, 2021)
This study evaluated the dietary supplementation of ginger Zingiber officinale essential oil for the Neotropical catfish Pseudoplatystoma reticulatum, its effects on fish hematology, immunology, the response of these variables to induction of stress (exposition to air for 3 min), and a bacterial challenge with Aeromonas hydrophila, and the effects on liver histomorphometry. Three levels of the ginger essential oil were evaluated (0.5, 1.0 and 1.5%) in addition to a control group (0%) in a feeding trial for 65 days in triplicate. Fish hematology and immunology were assessed at five different moments: after the feeding trial (0), after the stress induction (stress), and three points after the bacterial challenge (3, 6 and 24 h post-challenge). Fish fed the ginger essential oil supplemented diets did not exhibit significant differences between the hematocrit at the 0-sample point and the 24 h post-challenge point (P ≥ 0.05), while fish fed the control diet presented significantly lower values for the hematocrit when comparing those same two moments (P < 0.05). The thrombocytes count for fish fed the 0.5% essential oil supplemented diet was significantly higher than all other groups after the feeding trial (P < 0.05), and their total leukocytes count after the stress induction was also significantly higher than the other treatments (P < 0.05). Although the results mentioned above indicate that the ginger essential oil had positive health effects on the fish, no significant differences in survival after the challenge with A. hydrophila were observed (P ≥ 0.05). Lastly, histomorphometry suggests that the essential oil did not negatively impact fish hepatocytes.
Keywords: Aeromoniasis; Bacterial challenge; Feed additive; Hematology; Hepatocyte; Immunology; Pseudoplatystoma reticulatum